Introduction to Advanced Food Process Engineering - Sahu, Jatindra Kumar (CRC, 2014)
"Discussing recent advances in food processing technologies that allow for more energy efficient, cost effective, and healthier foods, this book examines the basic principles and major applications of advanced thermal and non-thermal techniques and equipment. Highlighting the growing sophistication of levels of control that reduce cycle time and improve product quality, the author reviews recent research, emphasizes the derivation and application of novel concepts, and provides solved problems and case studies for better understanding of the techniques"--